2014
DOI: 10.1007/s10916-014-0076-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relationship between Technology Readiness and Continuance Intention in an E-Appointment System: Relationship Quality as a Mediator

Abstract: Numerous types of self-service technologies have prevailed due to innovations in network and information technology. To hospitals, patient intentions to continue to use the e-appointment system are crucial. Previous investigations discussed only the relationships between the technology readiness of users and their continuance intentions, and ignored the most important mediator, relationship quality. This study explored the relationships among technology readiness, relationship quality, and continuance intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 61 publications
2
31
0
1
Order By: Relevance
“…TR and TAM combination) where TR was a global measure (see 7 ), or to some previous studies in which TR was presented as 4 single sub-constructs (e.g. 28 ) or posited as second-order reflective construct (e.g. 44 ), our conceptualization of TR as a second-order formative construct may be a better representation for the theoretical content of TR as originally suggested by Parasuraman 5 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…TR and TAM combination) where TR was a global measure (see 7 ), or to some previous studies in which TR was presented as 4 single sub-constructs (e.g. 28 ) or posited as second-order reflective construct (e.g. 44 ), our conceptualization of TR as a second-order formative construct may be a better representation for the theoretical content of TR as originally suggested by Parasuraman 5 .…”
Section: Discussionmentioning
confidence: 93%
“…Lin and Hsieh 18 found that TR is "an important driver of SST-satisfaction". Some empirical studies also proved the positive impact of optimism and innovativeness dimensions of TR on satisfaction (see 16,27,28 ). Therefore, it is hypothesized: H1: TR has positive impact on customers' satisfaction in using SSTs Perceived value is the overall assessment of what is received and what is given 8 .…”
Section: The Effects Of Tr On Customer Satisfaction Perceived Valuementioning
confidence: 92%
See 1 more Smart Citation
“…This system, has advantages and features, including access to the system at any Copyright © 2018, Shiraz E-Medical Journal. This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/) which permits copy and redistribute the material just in noncommercial usages, provided the original work is properly cited time and any place, allowing the user to see the physicians' appointments (9), selection of the desired option, editing the recorded information, more favorable relationship between physician and patient, improvement of the efficiency and effectiveness of care (5), cost reduction (11)(12)(13)(14), reduction of the number and volume of employees (7), saving patient information for use in subsequent appointments (11), and reduction of the number of missed appointments (9,11,(13)(14)(15)(16)(17)(18). However, despite the importance of this system, a few studies have been done on its evaluation and existing researches in this field have investigated topics, such as designing a web-based appointment system (19), patient satisfaction of online appointment booking systems (4,20), development of information technology acceptance model for an online appointment booking system in hospitals (21)(22)(23), implementation and use of the online appointment booking system in clinics (15,20), and improving the management of appointments (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Lin and Hsieh (2006) demonstrated that increased technological readiness of users positively influenced their behaviour intention and the service quality instituting technological readiness is an important driver of technology adoption and reuse. However, in the study of e-appointments made by patients, Chen et al (2014) showed that discomfort and insecurity were not major issues for technology users and they hypothesised it was due to the ubiquity of Internet use. This finding supports previous research that endorses each construct in TR may not be relevant when technology is ubiquitous.…”
Section: Technological Readinessmentioning
confidence: 99%